2016
DOI: 10.1589/jpts.28.2114
|View full text |Cite
|
Sign up to set email alerts
|

EMG activity of the serratus anterior and trapezius muscles during the different phases of the push-up plus exercise on different support surfaces and different hand positions

Abstract: [Purpose] The appropriate exercise prescription is crucial for achieving scapular stability and providing successful rehabilitation, and the Push-up Plus (PuP) exercise has an important role in shoulder rehabilitation. Consequently, this study examined the effect of support surface stability, hand positioning, and phase of exercise, on the trapezius and serratus anterior muscle contractions as well as on the EMG ratio of the upper/lower trapezius. [Subjects and Methods] Thirteen healthy male volunteers partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 15 publications
0
38
0
2
Order By: Relevance
“…Investigators 29,49 have also demonstrated that lower extremity a Each item was scored as 1 (yes) or 0 (no or not stated) based on whether the study included information about the criterion. higher pectoralis major and triceps activity 30% wider shoulder width: higher UT : LT ratio Gioftsos et al 15 (2016)…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Investigators 29,49 have also demonstrated that lower extremity a Each item was scored as 1 (yes) or 0 (no or not stated) based on whether the study included information about the criterion. higher pectoralis major and triceps activity 30% wider shoulder width: higher UT : LT ratio Gioftsos et al 15 (2016)…”
Section: Discussionmentioning
confidence: 98%
“…Seven articles discussed the effects of PUP variations (eg, different upper extremity, 31,47,48,50 lower extremity, 29,49 and PUP 8 positions) on training the SA and UT. Eleven articles 9,[15][16][17][18][19][20][21][22][23]52 focused on the effects of the base of support for PUP exercises. From our systematic review, we determined a suitable exercise prescription for training the SA and UT using PUP variations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations